'Journeying is Hard': Difficulty, Race and Poetics in Sarah Howe's Loop of Jade. Issue 1 (15th April 2020) - Chan, Mary Jean
Abstract : Amidst a growing consensus among critics that a discussion on race and white privilege in British poetry is long overdue, few have theorized on race and racism in relation to contemporary British BAME poets and their concomitant poetics. In being attentive to how BAME poets continue to be routinely othered by various critics, I will reflect on my positionality as a BAME poet-critic who considers literary criticism to be a crucial means to respond to exemplary work being produced by contemporary British BAME poets, with the aim of disseminating contemporary BAME poetry in forums which are less welcoming to non-white or non-Eurocentric voices and perspectives. This article will examine whether parody can be construed as a form of resistance, which can be deployed to counter racialized/racist notions of difficulty, readability and authenticity. As the case study of my exploration of contemporary British-Chinese poetry, Sarah Howe's Loop of Jade will be closely read to illuminate the inextricable 'connection between texts and the existential actualities of human life, politics, societies and events'.1 Through offering a textual analysis of Howe's collection with due attention to her politics and poetics, I aim to reveal how Loop of Jade has broadened the definition of linguistic innovation in contemporary British poetry and practice through its scintillating use of parody and hybrid poetics.